2018
DOI: 10.5152/tud.2018.49321
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA and detection of DNA fragmentations in sperm

Abstract: The questionable effectiveness of routine sperm parameters in determining male factor infertility problems and increasing the success rates of assisted reproductive techniques have led to the investigation of more detailed sperm parameters that could affect the male fertility and reproduction. Thus, the effects of different sperm parameters such as sperm DNA integrity was started to be investigated thanks to the previously described methods such as single cell gel electrophoresis (COMET) assay, sperm chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Sperm DNA damage can evaluated using AO staining (Kucuk, 2018). This study indicated that all frozen semen in the various diluents had low sperm-DNA damage.…”
Section: Tasj-36996mentioning
confidence: 91%
“…Sperm DNA damage can evaluated using AO staining (Kucuk, 2018). This study indicated that all frozen semen in the various diluents had low sperm-DNA damage.…”
Section: Tasj-36996mentioning
confidence: 91%
“…The TUNEL test generally consists of the fixation and permeabilization of sperm, the marking of DNA fragments, staining, and the evaluation of the stages of sperm. In the evaluation process, the sperm can be assessed subjectively under light and fluorescence microscopy or by flow cytometry [ 28 ]. The TUNEL assay can also be used to identify apoptotic cells in the tissues during histological examinations.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to correlate routinely evaluated sperm parameters at the moment of thawing with sperm viability and sperm DNA fragmentation evaluations, which together are able to correctly qualify an ideal sperm for fertilization. In the comet assay, sperm cells are placed on agarose gel using glass slides and, after cell discharge and DNA denaturation, alkaline electrophoresis is performed (Beirão, Cabrita, Soares, Herráez, & Dinis, 2008;Küçük, 2018;Lee & Steinert, 2003). The technique is based on different electrophoretic DNA patterns obtained from DNA fragments, where cells (DNA spermatozoa) with DNA archived in a comet-like tail structure are observed, larger when the DNA structure damage is greater (Gallego & Asturiano, 2018).…”
Section: Introductionmentioning
confidence: 99%